Sclerostin is expressed in articular cartilage but loss or inhibition does not affect cartilage remodeling during aging or following mechanical injury1. Issue 3 (25th February 2013) - Roudier, Martine; Li, Xiaodong; Niu, Qing‐Tian; Pacheco, Efrain; Pretorius, James K.; Graham, Kevin; Yoon, Bo‐Rin P.; Gong, Jianhua; Warmington, Kelly; Ke, Hua Z.; Black, Roy A.; Hulme, Joanne; et al.
Abstract: Objective: Sclerostin plays a major role in regulating skeletal bone mass, but its effects in articular cartilage are not known. The purpose of this study was to determine whether genetic loss or pharmacologic inhibition of sclerostin has an impact on knee joint articular cartilage. Methods: Expression of sclerostin was determined in articular cartilage and bone tissue obtained from mice, rats, and human subjects, including patients with knee osteoarthritis (OA). Mice with genetic knockout (KO) of sclerostin and pharmacologic inhibition of sclerostin with a sclerostin‐neutralizing monoclonal antibody (Scl‐Ab) in aged male rats and ovariectomized (OVX) female rats were used to study the effects of sclerostin on pathologic processes in the knee joint. The rat medial meniscus tear (MMT) model of OA was used to investigate the pharmacologic efficacy of systemic Scl‐Ab or intraarticular (IA) delivery of a sclerostin antibody–Fab (Scl‐Fab) fragment. Results: Sclerostin expression was detected in rodent and human articular chondrocytes. No difference was observed in the magnitude or distribution of sclerostin expression between normal and OA cartilage or bone. Sclerostin‐KO mice showed no difference in histopathologic features of the knee joint compared to age‐matched wild‐type mice. Pharmacologic treatment of intact aged male rats or OVX female rats with Scl‐Ab had no effect on morphologic characteristics of the articular cartilage. In the rat MMT model, pharmacologic treatment of animals with either systemic Scl‐Ab or IA injection of Scl‐Fab had no effect on lesion development or severity. Conclusion: Genetic absence of sclerostin does not alter the normal development of age‐dependent OA in mice, and pharmacologic inhibition of sclerostin with Scl‐Ab has no impact on articular cartilage remodeling in rats with posttraumatic OA.